Proceso logístico en la Empresa Transplipor - Guerra Moreira, María Alejandra (2021)
The present case study aims to analyze the operation of the logistics process in the company Transpliplor SA, located in the city of Guayaquil, is a financial entity in which its economic activity corresponds to providing heavy cargo transportation services, in charge of the transportation of the merchandise of the banana exporting company "Sabrostar Fruit Company". This work shows how Transplipor has some drawbacks in its logistics processes, such as in the case that the transporters do not comply with the arrival time when the merchandise must be at the port. For the development of the research, the line of "Financial, administrative, tax, auditing, control interlaced with the sub-line companies and public and private institutions" was carried out, together with the type of "quantitative and qualitative" methodology that served as support for the collection of information, accompanied by the instruments of the "survey" and the "interview" which allowed to store the data required to carry out the present investigation.